Flavour Components of Whiskey. III. Ageing Changes in the Low-Volatility Fraction - MacNamara, K.; van Wyk, C.J.; Brunerie, P.; Augustyn, O.P.H.; Rapp, A. (South African Journal of Enology and Viticulture, 2017)
The low-volatility wood-originating compounds isolated from whiskey by vacuum fractional distillation were analysed by high-resolution gas chromatography and mass spectrometry (GC-MS). Three phenolic esters previously unreported in whiskey were identified and confirmed by synthesis. Formation profiles for sixteen compounds were established in whiskeys aged for periods from 1.5 to 10 years in second-fill heavy-charred American Bourbon barrels. These profiles indicated significant increases for several compounds, especially in the older whiskeys. Ratios of aromatic phenolic aldehydes, and similar ratio changes during ageing, were different from reported data relating to other wood types and treatments. Further preparative separation by high-pressure liquid chromatography (HPLC) of the wood fraction followed by GC-MS allowed retention and mass spectral characterisation of additional compounds originating from wood. Sensory investigation indicated different and unique contributions from the HPLC cuts. Spiking of the three phenolic esters into a young whiskey gave a detectable increase in maturation intensity.